Epidemiology of chronic liver disease mortality in community population - Turin, TC; Rumana, N (Journal of Institute of Medicine Nepal, 2007)
Background: Liver disease is an important cause of morbidity and mortality in the United States. Currently, up to 2% of all deaths are attributable to liver disease. The economic burden associated with liver disease is also substantial. There are still significant gaps in the current understanding of the epidemiology and burden of liver disease at the population level. Materials and Methods: We studied chronic liver disease (CLD) and cirrhosis deaths among a community population of the state of Wisconsin for the duration of 1999-2005 to estimate the mortality and disease burden of CLD. Data information was gathered from the population based public data source; Wisconsin Interactive Statistics on Health. Results: A total of 3024 deaths were recorded due to CLD the study period of 1999-2005. The mortality rate was 7.92 per 100,000 person-year (95%CI :7.64–8.21). Male had higher mortality compared to female. Though statistically insignificant, a trend of increase in mortality rate was observed from 1999 (4.81, 95%CI:4.17–5.44) to 2005 (6.02, 95%CI:5.33–6.21). Conclusion: The findings were suggestive that the death due to CLD causes noteworthy burden for the population in terms of years of potential life lost. Prevention programme addressing this very problem should be accentuated. Key words: chronic liver disease, cirrhosis, mortality, disease-burden. The full text of this paper is available at Journal of Institute of Medicine website